Synchronization and stability in automotive transportation networks - Florian Klug (Naval Research Logistics (NRL), 2022)
The aim of this study was to analyze and evaluate synchronization and stability issues for the planning, operation, and control of processes in automotive transportation networks. We modeled transportation networks by using a coupled oscillator network based on a modified Kuramoto model. Each transport process was mapped as a phase oscillator indicating the transport time, period, and delay. The method could be applied to complex networks where it has not been possible to find analytical solutions. The novel generic oscillator approach was then applied to two transport topologies, namely, milk-run and just-in-sequence transport, based on real-world problems from a German car manufacturer. We conducted a detailed study of the parameter regions where different synchronization regimes occurred and investigated how the topology influenced the stability and dynamic behavior of transport networks. In particular, we focused on how transport period offsets and transport delays affected synchronous states. We showed that by the introduction of a transport synchronization matrix, the synchronization states in a transport network could be represented in a compact and comprehensive manner. Moreover, thresholds for round-trip stability could be calculated by analyzing the phase decoupling of a milk-run. These results were used for the vehicle route planning of milk-runs with synchronization constraints. Furthermore, the influence of the time delay of a track and trace system on the transport synchronization was analyzed. Finally, for the subsequent investigation of a just-in-sequence transport network, we showed how an adaptive control mechanism could re-synchronize an out-of-tune delivery process.
Keywords: 650; just-in-sequence transport; network synchronization; track and trace system; transport planning; transportation networks; vehicle routing